Preparation method of pearl layered montmorillonite-based inorganic insulating film
Preparation of pearl-layered montmorillonite-based inorganic insulating films through vacuum-assisted self-assembly and thermal coupling technology, solving the problem of insufficient mechanical and electrical insulation performance of existing materials in extreme environments, and achieving high-performance corona resistance and resistance Corona time is prolonged.
Patent Information
- Application Number
- CN202411248736.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-06
AI Technical Summary
The existing electrical insulating materials show insufficient mechanical properties, poor electrical insulation properties, unsuitable thickness in miniaturized high-power equipment in extreme environments, and insufficient corona resistance.
Using vacuum-assisted self-assembly and thermal coupling technology, two-dimensional nanomontmorillonite dispersion was prepared by chemical-mechanical peeling method, and after coating with polyvinylidene fluoride-hexafluoropropylene, it was vacuum suction filtration and hot pressing to form A pearl-layered montmorillonite-based inorganic insulating film enhances its orientation and density.
The nonlinear conductivity characteristics, breakdown field strength and corona resistance time of the material are significantly improved. The nonlinear coefficient reaches 10.66, the maximum breakdown field strength is 224.3kV/mm, and the corona resistance time reaches 1287.6 minutes, satisfying the miniaturization and high power Insulation requirements for electrical equipment.
Smart Images

Figure CN119170361A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of anti-corona insulating materials, and particularly relates to a method for preparing a nacreous montmorillonite-based inorganic insulating film. Background Art
[0002] With the rapid development of my country's modern power system and deep space exploration, modern electrical equipment is rapidly evolving towards miniaturization and high power. This trend has put forward more stringent requirements on electrical insulation materials, especially in terms of insulation reliability. Although the application and development of traditional materials such as metals, ceramics, mica paper and polymers in extreme environments have been studied, they each have their own limitations. Although metal and ceramic materials have excellent mechanical properties and can withstand extreme environments, metals are limited by their high density, and ceramics are difficult to shape due to their brittleness. On the other hand, although mica paper has excellent electrical insulation properties, thermal stability and chemical stability, it has poor micro-uniformity and low stress transfer efficiency between micro-components, resulting in insufficient mechanical properties and dielectric strength, and the thickness is too large, which is not suitable for miniaturized high-power electrical equipment. Although polymer materials are uniform, lightweight, thin and have good ductility, they generally have insufficient anti-corona capabilities. Materials selected by nature are often regarded as the source of inspiration for high-performance and high-efficiency solutions because of their continuous optimization during evolution. It is crucial to develop new structural materials that have both excellent performance and meet the requirements of sustainable development by deeply studying the formation mechanism and self-assembly process of biomaterials in nature. Summary of the invention
[0003] In order to overcome the deficiencies of the above-mentioned prior art, the purpose of the present invention is to provide a method for preparing a nacreous montmorillonite-based inorganic insulating film. Aiming at the deficiencies in the prior art, the research idea is to regulate the orientation, order, density and interface interaction of the two-dimensional nanomaterial structure, and adopt a typical natural two-dimensional layered nanomaterial montmorillonite. By utilizing vacuum-assisted self-assembly and thermal coupling technology, an inorganic insulating film with nonlinear conductivity properties is prepared, which has high anti-corona properties.
[0004] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing a nacreous montmorillonite-based inorganic insulating film, comprising the following steps: Step 1, preparing the following raw materials: montmorillonite, N-methyl-2-pyrrolidone, polyvinylpyrrolidone, polyvinylidene fluoride-hexafluoropropylene; Step 2, preparation of two-dimensional nano-montmorillonite dispersion; Step 3, coating with polyvinylidene fluoride-hexafluoropropylene; Step 4, forming the inorganic insulating film; Step 5, drying the inorganic insulating film; Step 6: thermal-mechanical coupling treatment of the inorganic insulating film.
[0005] In the step 1, the montmorillonite is an unstripped sodium-based montmorillonite raw material.
[0006] In step 2, the two-dimensional nano-montmorillonite dispersion is prepared by chemical-mechanical exfoliation method, and the specific steps are: 1.5-2.5 g of montmorillonite raw material is dissolved in 300-500 mL of N-methyl-2-pyrrolidone solution and magnetically stirred for 10-20 min to obtain a montmorillonite dispersion, and then 18-30 g of polyvinyl pyrrolidone is slowly added, stirring is continued for 12-20 h, and then allowed to stand for 48-72 h, and the supernatant is taken to obtain a two-dimensional nano-montmorillonite dispersion.
[0007] The montmorillonite raw material is dried in a forced air drying oven at 80-90° C. for 6-8 hours in advance to remove residual moisture.
[0008] The speed of the magnetic stirring is 3000-3200 rpm.
[0009] The polyvinyl pyrrolidone is divided into three equal parts, and each part is added slowly at intervals of 5-7 minutes.
[0010] In the step 3, the coating of polyvinylidene fluoride-hexafluoropropylene is to add 1%-5% of the mass of nano-montmorillonite polyvinylidene fluoride-hexafluoropropylene to the two-dimensional nano-montmorillonite dispersion, and then ultrasonically treat for 30-40 minutes, and continue stirring for 1-2 hours to obtain a two-dimensional nano-montmorillonite dispersion coated with polyvinylidene fluoride-hexafluoropropylene.
[0011] In step 4, the inorganic insulating film is formed by using a vacuum filtration device to filter the two-dimensional nano-montmorillonite dispersion coated with polyvinylidene fluoride-hexafluoropropylene, and using the directional flow rate of the liquid to orient the nanosheets so that they are arranged in parallel on filter paper with an average pore size of 220 μm to obtain a wet inorganic insulating film.
[0012] In the step 5, the inorganic insulating film is dried by placing the wet film in a forced air drying oven at 80-90° C. for 6-8 hours.
[0013] The step 6, the thermal coupling treatment of the inorganic insulating film is to place the film dried in step 5 on a hot press, and hot press for 30-50 minutes at a temperature of 180-200°C and a pressure of 18-20Mpa to finally obtain a montmorillonite inorganic insulating film with a nacreous structure.
[0014] The present invention adopts a bionic manufacturing strategy, which is expected to gradually replace the traditional manufacturing method of insulating materials. The core of this strategy is to imitate the hierarchical structure and interface interaction of biological materials in nature to achieve the multifunctionalization of artificial materials. By carefully designing the microstructure of the material, the material performance can be significantly improved. In this process, the use of nano-host materials with different functions gives the composite material more intelligent characteristics, and this strategy has good universality and can be better used on two-dimensional nanomaterials; by accurately controlling the arrangement and distribution of two-dimensional nanomaterials, the key properties of the composite material such as mechanical properties, thermal stability, and electrical conductivity can be effectively optimized, thereby promoting the development of high-performance composite materials. For example, materials such as graphene with excellent electrical conductivity and montmorillonite nanosheets with flame retardant properties can be used as reinforcing phases, which not only enhance the mechanical properties of the base material, but also provide additional functions such as electrical conductivity or flame retardancy. The realization of this intelligent functionality depends on the synergistic effect between nanomaterials and the matrix, as well as the interface engineering at the nanoscale. By accurately controlling the dispersibility, interface compatibility and interaction force of the nano-components, the overall performance of the composite material can be optimized, so that it performs well in a specific application environment.
[0015] The beneficial effects of the present invention are: Compared with the prior art, the present invention combines vacuum-assisted self-assembly with thermal coupling to construct a pearl-like layered structure, and simultaneously adds polyvinylidene fluoride-hexafluoropropylene in the film-forming process to increase the interlayer effect of nanosheets, reduce defects, and prepare an anti-corona inorganic insulating film with nonlinear conductivity characteristics. Vacuum-assisted self-assembly can improve the orientation of nanosheets, maximize the two-dimensional characteristics of nanosheets, and the parallel stacking arrangement of two-dimensional nanosheets maximizes the dielectric strength perpendicular to the cleavage surface of the nanosheets. Thermal coupling technology can further increase the density between the sheets and improve the insulating properties of the material. Through the above-mentioned treatment, the inorganic insulating film with a pearl-like layered structure finally obtained by the present invention has a nonlinear coefficient of up to 10.66, a breakdown field strength of up to 224.3kV / mm, and a corona resistance time of 1287.6min at a field strength of 80kV / mm. The conductivity and nonlinear coefficient of the film can be changed by adjusting the content of polyvinylidene fluoride-hexafluoropropylene, so it can be applied in different practical occasions. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The present invention is a flow chart for preparing the nacreous montmorillonite-based inorganic insulating film.
[0017] Figure 2 This is a physical picture of the nacreous montmorillonite-based inorganic insulating film obtained in Example 1 of the present invention.
[0018] Figure 31 is a cross-sectional scanning electron microscope image of the nacreous montmorillonite-based inorganic insulating film obtained in Example 1 of the present invention.
[0019] Figure 4 1 is a graph showing the nonlinear conductivity characteristics of the nacreous montmorillonite-based inorganic insulating films obtained in Example 1, Example 2, Example 3 and Comparative Example 1 of the present invention.
[0020] Figure 5 3 is a breakdown characteristic diagram of the nacreous montmorillonite-based inorganic insulating films obtained in Example 1, Example 2, Example 3 and Comparative Example 1 of the present invention.
[0021] Figure 6 It is a corona resistance bar graph of the nacreous montmorillonite-based inorganic insulating films obtained in Example 2 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0022] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention.
[0023] A method for preparing a pearly montmorillonite-based inorganic insulating film comprises the following steps: firstly dissolving a montmorillonite raw material in N-methyl-2-pyrrolidone and stirring the mixture evenly; then adding polyvinyl pyrrolidone and continuing stirring the mixture, and obtaining a two-dimensional nano-montmorillonite dispersion after standing; then adding a small amount of polyvinylidene fluoride-hexafluoropropylene and subjecting the mixture to ultrasonic stirring treatment to form a novel dispersion; preparing a wet inorganic insulating film through vacuum-assisted self-assembly technology; drying the film and then subjecting the film to a hot pressing treatment to finally obtain a montmorillonite-based inorganic insulating film having a pearly layer structure; Example
[0024] A method for preparing a nacreous montmorillonite-based inorganic insulating film is prepared by combining vacuum-assisted self-assembly and thermal coupling technology, comprising the following steps: Step 1, preparing the following raw materials: including unpeeled sodium montmorillonite raw material, N-methyl-2-pyrrolidone, polyvinylpyrrolidone, and polyvinylidene fluoride-hexafluoropropylene; Step 2, the two-dimensional nano-montmorillonite is prepared by chemical-mechanical exfoliation, and the montmorillonite raw material is dried in a forced air drying oven at 80° C. for 6 hours in advance to remove residual moisture; 1.5 g of montmorillonite raw material was dissolved in 300 mL of N-methyl-2-pyrrolidone solution and magnetically stirred for 10 min at a speed of 3000 rpm to obtain a montmorillonite dispersion; 18 polyvinyl pyrrolidone was divided into three equal parts, each part was slowly added into the montmorillonite dispersion at intervals of 5 minutes, stirring was continued for 12 hours, and then allowed to stand for 48 hours, and the supernatant was taken to obtain a two-dimensional nano-montmorillonite dispersion.
[0025] Step 3, adding 1% of the mass of nano-montmorillonite polyvinylidene fluoride-hexafluoropropylene to the nano-montmorillonite dispersion, then ultrasonically treating for 30 minutes, and continuing to stir for 1 hour to obtain a two-dimensional nano-montmorillonite dispersion coated with polyvinylidene fluoride-hexafluoropropylene.
[0026] Step 4, using a vacuum filtration device to filter the polyvinylidene fluoride-hexafluoropropylene coated nano-montmorillonite dispersion, using the directional flow rate of the liquid to orient the nanosheets so that they are arranged in parallel on the filter paper with an average pore size of 220 μm, to obtain a wet inorganic insulating film.
[0027] Step 5, drying the wet film in a forced air drying oven at 80° C. for 6 hours.
[0028] Step 6, placing the dried film on a hot press, and hot pressing for 30 minutes at a temperature of 180° C. and a pressure of 18 MPa, to finally obtain a montmorillonite inorganic insulating film with a layered structure.
[0029] Figure 2 This is a real picture of the nacreous montmorillonite-based inorganic insulating film obtained in Example 1 of the present invention. It can be seen from the figure that the surface of the inorganic film is smooth and has a certain degree of flexibility.
[0030] Figure 3 This is a cross-sectional scanning electron microscope image of the nacreous montmorillonite-based inorganic insulating film obtained in Example 1 of the present invention. From the microscopic morphology of the cross section, it can be seen that the inorganic insulating film is composed of countless montmorillonite nanosheets tightly arranged to form a parallel stacked layered structure, similar to the structure of nacre. This structure not only presents a high degree of order, but also the tight stacking method gives the material excellent insulating properties. Example
[0031] A method for preparing a nacreous montmorillonite-based inorganic insulating film comprises the following steps: Step 1, preparing the following raw materials: including unpeeled sodium montmorillonite raw material, N-methyl-2-pyrrolidone, polyvinylpyrrolidone, and polyvinylidene fluoride-hexafluoropropylene; Step 2, the two-dimensional nano-montmorillonite is prepared by chemical-mechanical exfoliation, and the montmorillonite raw material is dried in a forced air drying oven at 85° C. for 7 hours in advance to remove residual moisture; 2 g of montmorillonite raw material was dissolved in 400 mL of N-methyl-2-pyrrolidone solution and magnetically stirred for 15 min at a speed of 3100 rpm to obtain a montmorillonite dispersion; 24 g of polyvinyl pyrrolidone was divided into three equal parts, each part was slowly added to the montmorillonite dispersion at intervals of 6 minutes, stirring was continued for 16 hours, and then allowed to stand for 60 hours, and the supernatant was taken to obtain a two-dimensional nano-montmorillonite dispersion.
[0032] Step 3, adding 3% of the mass of nano-montmorillonite polyvinylidene fluoride-hexafluoropropylene to the nano-montmorillonite dispersion, and then ultrasonically treating for 35 minutes and stirring for 1.5 hours to obtain a two-dimensional nano-montmorillonite dispersion coated with polyvinylidene fluoride-hexafluoropropylene.
[0033] Step 4, using a vacuum filtration device to filter the polyvinylidene fluoride-hexafluoropropylene coated nano-montmorillonite dispersion, using the directional flow rate of the liquid to orient the nanosheets so that they are arranged in parallel on the filter paper with an average pore size of 220 μm, to obtain a wet inorganic insulating film.
[0034] Step 5, drying the wet film in a forced air drying oven at 85° C. for 7 hours.
[0035] Step 6, placing the dried film on a hot press, hot pressing for 40 minutes at a temperature of 190° C. and a pressure of 19 MPa, and finally obtaining a montmorillonite inorganic insulating film with a layered structure. Example
[0036] A method for preparing a nacreous montmorillonite-based inorganic insulating film comprises the following steps: Step 1, preparing the following raw materials: including unpeeled sodium montmorillonite raw material, N-methyl-2-pyrrolidone, polyvinylpyrrolidone, and polyvinylidene fluoride-hexafluoropropylene; Step 2, the two-dimensional nano-montmorillonite is prepared by chemical-mechanical exfoliation, and the montmorillonite raw material is dried in a 90° C. forced air drying oven for 8 h in advance to remove residual moisture; 2.5 g of montmorillonite raw material was dissolved in 500 mL of N-methyl-2-pyrrolidone solution and magnetically stirred at a speed of 3200 rpm for 20 min to obtain a montmorillonite dispersion; 30 g of polyvinyl pyrrolidone was divided into three equal parts, each part was slowly added to the montmorillonite dispersion at intervals of 7 minutes, stirring was continued for 20 hours, and then allowed to stand for 72 hours, and the supernatant was taken to obtain a two-dimensional nano-montmorillonite dispersion.
[0037] Step 3, adding 5% polyvinylidene fluoride-hexafluoropropylene by mass of the nano-montmorillonite to the nano-montmorillonite dispersion, then ultrasonically treating for 40 minutes, and continuing to stir for 2 hours to obtain a two-dimensional nano-montmorillonite dispersion coated with polyvinylidene fluoride-hexafluoropropylene; Step 4, using a vacuum filtration device to filter the polyvinylidene fluoride-hexafluoropropylene coated nano-montmorillonite dispersion, using the directional flow rate of the liquid to orient the nanosheets so that they are arranged in parallel on the filter paper with an average pore size of 220 μm, to obtain a wet inorganic insulating film.
[0038] Step 5: Dry the wet film in a 90° C. forced air drying oven for 8 h.
[0039] Step 6, placing the dried film on a hot press, and hot pressing for 50 minutes at a temperature of 200° C. and a pressure of 20 MPa, to finally obtain a montmorillonite inorganic insulating film with a layered structure.
[0040] Comparative Example 1 In the preparation process of the montmorillonite-based inorganic insulating film, polyvinylidene fluoride-hexafluoropropylene is not added, and a pure montmorillonite inorganic film comparison sample is prepared. The specific steps are as follows: Step 1, preparing the following raw materials: including unpeeled sodium montmorillonite raw material and N-methyl-2-pyrrolidone; Step 2, preparation of a two-dimensional nano-montmorillonite dispersion, wherein the two-dimensional nano-montmorillonite is prepared by a chemical-mechanical exfoliation method, and the montmorillonite raw material is dried in a forced air drying oven at 80° C. for 6 hours in advance to remove residual moisture; 1.5 g of montmorillonite raw material was dissolved in 300 mL of N-methyl-2-pyrrolidone solution and magnetically stirred for 10 min at a speed of 3000 rpm to obtain a montmorillonite dispersion; 18g of polyvinyl pyrrolidone was divided into three equal parts, and each part was slowly added to the montmorillonite dispersion at intervals of 5 minutes, and the mixture was stirred for 12 hours, and then allowed to stand for 48 hours, and the supernatant was taken to obtain a two-dimensional nano-montmorillonite dispersion; Step 3, using a vacuum filtration device to filter the nano-montmorillonite dispersion, using the directional flow rate of the liquid to orient the nanosheets so that they are arranged in parallel on the filter paper with an average pore size of 220 μm, to obtain a wet inorganic insulating film.
[0041] Step 4: Dry the wet film in a forced air drying oven at 80° C. for 6 hours.
[0042] Step 5, placing the dried film on a hot press, and hot pressing for 30 minutes at a temperature of 180° C. and a pressure of 18 MPa, to finally obtain a montmorillonite inorganic insulating film with a layered structure.
[0043] Figure 4 The nonlinear characteristic curves of the nacreous montmorillonite-based inorganic insulating films obtained in Example 1, Example 2, Example 3 and Comparative Example 1 of the present invention are shown in the figure. It can be seen from the figure that the inorganic film has obvious nonlinear conductivity characteristics. After adding polyvinylidene fluoride-hexafluoropropylene, the conductivity and nonlinear coefficient β With further increase, the nonlinear coefficient reaches a maximum of 10.66.
[0044] Figure 5The breakdown characteristic curves of the nacreous montmorillonite-based inorganic insulating films obtained in Example 1, Example 2, Example 3 and Comparative Example 1 of the present invention are shown in the figure. As can be seen from the figure, the breakdown field strength of the inorganic film after adding polyvinylidene fluoride-hexafluoropropylene reaches a maximum of 224.3 kV / mm, showing excellent insulation properties.
[0045] Figure 6 The figure is a bar graph of the corona resistance time of the nacreous montmorillonite-based inorganic insulating film obtained in Example 2 of the present invention and Comparative Example 1. It can be seen from the figure that the corona resistance time of the inorganic film is increased by 58.8% after adding polyvinylidene fluoride-hexafluoropropylene, showing excellent anti-corona properties.
Claims
1. A method for preparing a nacreous montmorillonite-based inorganic insulating film, characterized in that: The following steps are involved: Step 1, prepare the following raw materials: montmorillonite, N-methyl-2-pyrrolidone, polyvinylpyrrolidone, polyvinylidene fluoride-hexafluoropropylene; Step 2, preparation of two-dimensional nano-montmorillonite dispersion; Step 3, coating with polyvinylidene fluoride-hexafluoropropylene; Step 4, forming the inorganic insulating film; Step 5, drying the inorganic insulating film; Step 6: thermal-mechanical coupling treatment of the inorganic insulating film.
2. The method for preparing a nacreous montmorillonite-based inorganic insulating film according to claim 1, characterized in that: In the step 1, the montmorillonite is an unstripped sodium-based montmorillonite raw material.
3. The method for preparing a nacreous montmorillonite-based inorganic insulating film according to claim 1, characterized in that: In step 2, the two-dimensional nano-montmorillonite dispersion is prepared by chemical-mechanical exfoliation method, and the specific steps are: 1.5-2.5 g of montmorillonite raw material is dissolved in 300-500 mL of N-methyl-2-pyrrolidone solution and magnetically stirred for 10-20 min to obtain a montmorillonite dispersion, and then 18-30 g of polyvinyl pyrrolidone is slowly added, stirring is continued for 12-20 h, and then allowed to stand for 48-72 h, and the supernatant is taken to obtain a two-dimensional nano-montmorillonite dispersion.
4. The method for preparing a nacreous montmorillonite-based inorganic insulating film according to claim 3, characterized in that: The montmorillonite raw material is dried in a forced air drying oven at 80-90° C. for 6-8 hours in advance to remove residual moisture.
5. The method for preparing a nacreous montmorillonite-based inorganic insulating film according to claim 3, characterized in that: The speed of the magnetic stirring is 3000-3200 rpm.
6. The method for preparing a nacreous montmorillonite-based inorganic insulating film according to claim 2, characterized in that: The polyvinyl pyrrolidone was divided into three equal parts, and each part was added slowly at intervals of 5 minutes.
7. The method for preparing a nacreous montmorillonite-based inorganic insulating film according to claim 1, characterized in that: In the step 3, the coating of polyvinylidene fluoride-hexafluoropropylene is to add 1%-5% of the mass of nano-montmorillonite polyvinylidene fluoride-hexafluoropropylene to the two-dimensional nano-montmorillonite dispersion, and then ultrasonically treat for 30-40 minutes, and continue stirring for 1-2 hours to obtain a two-dimensional nano-montmorillonite dispersion coated with polyvinylidene fluoride-hexafluoropropylene.
8. The method for preparing a nacreous montmorillonite-based inorganic insulating film according to claim 1, characterized in that: In step 4, the inorganic insulating film is formed by using a vacuum filtration device to filter the two-dimensional nano-montmorillonite dispersion coated with polyvinylidene fluoride-hexafluoropropylene, and using the directional flow rate of the liquid to orient the nanosheets so that they are arranged in parallel on filter paper with an average pore size of 220 μm to obtain a wet inorganic insulating film.
9. The method for preparing a nacreous montmorillonite-based inorganic insulating film according to claim 1, characterized in that: In the step 5, the inorganic insulating film is dried by placing the wet film in a forced air drying oven at 80-90° C. for 6-8 hours.
10. The method for preparing a nacreous montmorillonite-based inorganic insulating film according to claim 1, characterized in that: The step 6, the thermal coupling treatment of the inorganic insulating film is to place the film dried in step 5 on a hot press, and hot press for 30-50 minutes at a temperature of 180-200°C and a pressure of 18-20Mpa to finally obtain a montmorillonite inorganic insulating film with a nacreous structure.
Citation Information
Patent Citations
Method for preparing polyvinylidene fluoride polarizable film
CN101649058A
Method for preparing organic-inorganic nano-composite membranes by using layered inorganic nano particles
CN103801201A
Polyvinylidene fluoride composite material, preparation method and applications thereof
CN105385077A
Composite material having shell nacre-imitated layered structure as well as preparation method and application of composite material
CN105774182A
High-strength reddish transparent nacre-like composite film and preparation method thereof
CN106750570A
